Clinical characteristics and prognosis of non-B, non-C hepatocellular carcinoma: The impact of patient sex on disease-free survival - A retrospective cohort study. (March 2017) - Hashimoto, Masakazu; Tashiro, Hirotaka; Kobayashi, Tsuyoshi; Kuroda, Shintaro; Hamaoka, Michinori; Ohdan, Hideki
Abstract: Background: The number of patients with hepatocellular carcinoma (HCC) negative for both hepatitis B virus surface antigen (HBsAg) and hepatitis C virus antibody (HCVAb) has increased recently. The purpose of the present study was to investigate the clinical characteristics and prognoses of non-B non-C HCC (NBNC-HCC) patients. Materials and methods: From January 2000 to December 2013, 154 patients with NBNC-HCC and 560 patients with HBsAg or HCVAb positive (BC)-HCC who underwent curative resection were analyzed retrospectively. The clinical features of NBNC-HCC and BC-HCC were compared, and the prognoses of NBNC-HCC patients were analyzed. Results: In comparison to patients with BC-HCC, patients with NBNC-HCC had better liver function but higher pathological tumor stages. The disease-free survival (DFS) duration was significantly higher in patients with NBNC-HCC than it was in those with BC-HCC. In patients with NBNC-HCC, aspartate aminotransferase ≥40 IU/L, albumin level <3.5 g/dL, and multiple tumors were independent risk factors of overall survival; and male sex and multiple tumors were independent risk factors of DFS. Conclusion: Patients with NBNC-HCC had significantly longer DFS durations than those with BC-HCC. The patient sex had an impact on the postsurgical outcomes of patients with NBNC-HCC in DFS. Highlights: We compared the patients of non-B, non-C HCC (NBNC-HCC) with those of virus-related HCC. The DFS duration in patients with NBNC-HCC was longer than those with virus-related HCC. We showed the independent risk factors of overall survival and disease-free survival in NBNC-HCC.